Neurological Health in Sexual and Gender Minority Individuals - Simmasalam, Rubinee; Zuniga, Mary C.; Hinson, H.E. (Seminars in Neurology, 2024)
Despite representing a significant proportion of the U.S. population, there is a paucity of population-based research on the health status and health needs of sexual and gender minority (SGM) individuals in neurology. Compared with heterosexual peers, some SGM populations have a higher burden of chronic health conditions. In parallel, SGM individuals are more likely to experience stigma and discrimination producing psychological distress, which may contribute to and be compounded by reduced health care access and utilization. In this narrative review, we summarize the existing literature on common neurological health conditions such as stroke, headache, epilepsy, movement disorders, and traumatic brain injury through the lens of intersection of SGM identity. Special focus is attuned to social determinants of health and gender-affirming hormonal therapy. Given the limitations in the available literature, there is an urgent unmet need for datasets that include sexual orientation and gender identity information, as well as funding for research that will characterize the prevalence of neurological conditions, unique risk factors, and health outcomes in SGM populations. In the health care community, providers should address deficiencies in their professional training and integrate inclusive language into their clinical skillset to build trust with SGM patients. There is an opportunity in neurology to proactively engage SGM communities, collaborate to remove barriers to care, promote resilience, and develop targeted interventions to ensure high-quality, culturally competent care for SGM populations to improve neurological health for all.
Keywords: sexual and gender minority; sexual orientation; gender identity; neurology; gender affirming hormone therapy; stroke